Analyzing research trends in university student experience based on topic modeling - Hong, Seongyoun; Park, Taejung; Choi, Jaewon (Sustainability (Switzerland), 2020)
This study aims to identify research trends in student experience in higher education through analyzing the topics around which research on university students' experiences has been conducted. Using the topic modeling technique, the Scopus database for studies published up to 2017 containing the terms "student experience" and either "higher education" or "tertiary education" in their titles, keywords, and abstracts was searched. After excluding overlapping studies, a total of 1211 studies were extracted. The articles were then classified into a total of 21 topics on university student experience, including "Learning with online technologies", "Practice at the university", and "Diversity in college". The results of the current study indicate that it will be possible to offer various programs to support more valuable and better student experience at the university level. Thus, this study elucidates the ways in which research fields regarding student experience have been constructed and the ways in which the main research trends have changed.
Keywords: Comparative study; Research trends; Student experience; Text mining; Topic modeling